Association of candidate pharmacogenetic markers with platinum-induced ototoxicity: PanCareLIFE dataset - Langer, Thorsten; Clemens, Eva; Broer, Linda; Maier, Lara; Uitterlinden, André G.; de Vries, Andrica C.H.; van Grotel, Martine; Pluijm, Saskia F.M.; Binder, Harald; Mayer, Benjamin; von dem Knesebeck, Annika; Byrne, Julianne; et al. (Data in Brief, 2020)
Genetic association studies suggest a genetic predisposition for cisplatin-induced ototoxicity. Among other candidate genes, thiopurine methyltransferase (TPMT) is considered a critical gene for susceptibility to cisplatin-induced hearing loss in a pharmacogenetic guideline. The PanCareLIFE cross-sectional cohort study evaluated the genetic associations in a large pan-European population and assessed the diagnostic accuracy of the genetic markers. 1,112 pediatric cancer survivors who had provided biomaterial for genotyping were screened for participation in the pharmacogenetic association study. 900 participants qualified for inclusion. Based on the assessment of original audiograms, patients were assigned to three phenotype categories: no, minor, and clinically relevant hearing loss. Fourteen variants in eleven candidate genes (ABCC3, OTOS, TPMT, SLC22A2, NFE2L2, SLC16A5, LRP2, GSTP1, SOD2, WFS1, and ACYP2) were genotyped. The genotype and phenotype data represent a resource for conducting meta-analyses to derive a more precise pooled estimate of the effects of genes on the risk of hearing loss due to platinum treatment.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Adverse drug reaction; Cancer survivors; Childhood cancer; Cisplatin: carboplatin; Drug-induced ototoxicity; Genetic markers; Multicenter cohort study; Pharmacogenetics